PENGARUH PEMBELAJARAN PAI TERHADAP MOTIVASI BELAJAR PESERTA DIDIK - Ekania Sausan Zahro; Fikri Najmuddin Abdullah; Habib Al Ridho; Alhidayah Rizki Putra; Kamarul Huda; Etnida Wahyuni Hasibuan; Raja Nurmalita; Ruth Sabrina Br Hasibuan; Sabrun Jamil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
A fresh look at how lessons in faith shape student drive begins with quiet reflection. Because inner spark matters more than rote effort when schoolwork feels meaningful, attention turns to classroom moments rooted in belief. One way into this idea comes from gathering insights found in published works rather than live surveys or tests. Pages from trusted authors those who write textbooks, peer-reviewed articles, government records are pieced together like fragments of a larger picture. What holds these pieces is a shared thread: education shaped by religious values may quietly feed a learner's will to keep going. Not every page says the same thing, yet patterns emerge where meaning sticks. Looking at earlier research and theory, the information was studied through careful sorting methods. Not just isolated ideas, but links emerged between how religious classes are taught and what drives students to learn. When lessons feel relevant, when they mean something real in daily life, attention grows stronger. Teachers showing consistency in values matters too it adds weight, makes things stick. Motivation rises because of inner drive, yes but also from outside encouragement shaped by respect. Something deeper forms alongside: a sense of purpose rooted in faith. Learning begins to look different not only tasks to finish, yet acts tied to growth and devotion. This shift does not happen overnight, still it shows up clearly in patterns found here. Religious education isn’t separate from overall development it quietly holds everything together. Its effect runs wide, touching willpower, mindset, even long-term direction in school life.